FACTORS RELATED TO DISCLAIMER ATTITUDES TO PEOPLE WITH HIV AND AIDS (PLWHA) - Dian Ayu Lestari (Universitas Airlangga, 2021)
HIV/AIDS remain the most serious diseases worldwide. One of the efforts that health workers have made in health promotion using prevention and control. This study aims to determine the factors that interact with the attitude of PLWHA. This study used a descriptive analysis using the chi-square statistical test. The use of data is secondary data from 2017 Indonesian Demographic and Health Survey (IDHS). The results of statistical testing using the chi-square found that the factors that influence rejection attitudes in people with HIV/AIDS (PLWHA) are age (p = 0.001; λ = 0, 05), area of residence (p = 0.001; λ = 0.05), education (p = 0.001; λ = 0.05), and exposure to mass media (p = 0.001; λ = 0.05). From the results of statistical tests, it can be seen that attitudes towards PLWHA are influenced by age and area of residence.